(untitled) (The Review of Diabetic Studies, 2024)
The impact of medical device innovations on patient care extends far beyond clinical efficacy, demanding a multidisciplinary analysis to fully comprehend its complexities. From a psychological perspective, devices reshape patient autonomy, illness identity, and cognitive burden, influencing adherence and well-being. Nurses, as frontline integrators, navigate altered workflows and the imperative to balance technological data with empathetic, hands-on care, ensuring safety and preserving the human connection. Social workers highlight critical issues of equity and access, noting how socioeconomic barriers and the digital divide can transform innovations into sources of disparity, while also addressing the psychosocial support needs of device-dependent patients and families. Concurrently, health security experts underscore the paramount importance of cybersecurity in an interconnected ecosystem, where vulnerabilities in software and connectivity can directly threaten patient safety and privacy. Ultimately, a holistic model of responsible innovation is required, one that synthesizes these perspectives to ensure medical devices are not only technologically advanced but also psychologically supportive, practically manageable, socially equitable, and fundamentally secure, thereby truly enhancing holistic patient care.